KUALITAS PELAYANAN PASANG BARU LISTRIK PRABAYAR DI PT PLN (PERSERO) UNIT LAYANAN PELANGGAN WOHA - Sebtian Tri Putra; Ismunandar Ismunandar (Universitas Sarjanawiyata Tamansiswa, 2021)
The purpose of this study was to determine how the service quality of Prepaid Electricity Installations at PT PLN (Persero) WOHA Customer Service Unit. This type of research is descriptive, the data sources used are primary and secondary data. The research instrument used was a Likert scale questionnaire. The data collection techniques used were observation, interview, questionnaire, and literature study. The data analysis technique used is validity test, reliability test and one sample t test. The results showed that the service quality of prepaid electricity installations at PT. PLN Persero ULP. Woha more than 70% of expected (good).